Implications of biodiesel production for enhancing thermostable T1.2RQ lipase secretion in Pichia pastoris via chaperone co-expression - ESTI PUSPITASARI; YEPY HARDI RUSTAM; ANDREAS ADHI SATYA; ANTONIUS SUWANTO; ARIS TRI WAHYUDI; RIKA INDRI ASTUTI (Society for Indonesian Biodiversity, 2025)
Abstract. Puspitasari E, Rustam YH, Satya AA, Suwanto A, Wahyudi AT, Astuti RI. 2025. Implications of biodiesel production for enhancing thermostable T1.2RQ lipase secretion in Pichia pastoris via chaperone co-expression. Biodiversitas 26: 4557-4566. The thermostable T1.2RQ lipase from Geobacillus stearothermophilus (isolated from Indonesian hot springs) was expressed in Pichia pastoris GS115 via multicopy integration (6X). Co-expression of chaperones bmh2 (797 bp) and sso2 (875 bp) was achieved using Gibson Assembly and pPICZAwbe. Transformants GS115/T1.2RQ(6X)_bmh2#3 showed 71% higher activity (p = 0.017) versus controls, while sso2 reduced activity by 23% (p = 0.028). SDS-PAGE confirmed a 43 kDa band, and tributyrin assays verified extracellular secretion. In biodiesel trials, the lipase reduced Palm Fatty Acid Distillated Free Fatty Acid (PFAD FFA) to 4.9%, meeting SNI 7182:2015 standards. This study demonstrates bmh2’s role in alleviating Endoplasmic Reticulum (ER) stress and advancing bacterial lipase production in yeast, with applications in sustainable biodiesel.C) analysis showed methyl palmitate (C16:0) and methyl stearate (C18:0) as the dominant Fatty Acid Methyl Ester (FAME) species. This research demonstrates that bmh2 is the most effective chaperone for co-expression with a six-copy lipase, increasing extracellular activity. The enzyme produced by heterologous expression in Pichia can be used for lab-scale biodiesel production, comparable to that expressed in Escherichia coli. This is the first report of G. stearothermophilus T1.2RQ lipase, and these findings advance bacterial lipase gene expression research in the P. pastoris expression system. Future work should optimize tandem chaperone systems (bmh2 + PDI) and pilot-scale fermentation. This study underscores Indonesia’s microbial biodiversity as a resource for novel biocatalysts, aligning with Biodiversitas’s mission to bridge ecology and biotechnology.